Indicators of cytological composition of the nasal mucus in children with acute respiratory viral infection - O. I. Smiyan; Ye. V. Dmitrova; V. A. Smiyanov; O. P. Moshchich; I. Yu. Vysotskyi (Zaporožskij Medicinskij Žurnal)
Aim. To study the cellular composition of the nasal secretion in children with acute respiratory viral infections in the acute phase of the disease.